Gaya Hidup Masyarakat di Kawasan Weltevreden, Batavia Tahun 1900-1942 - Hibatullah, Muhammad Imam; Wijaya, Daya Negri (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
This paper describes the lifestyle of people living in the Weltevreden area, a district in the city of Batavia in the period 1900-1942. The lifestyle discussed includes language, clothing, music and entertainment, among others. The authors use the historical method to analyze textual sources and visual sources. Available sources include newspapers, books, photographs, official government records, and scientific articles. The results of this study show that Indis culture which developed on the island of Java since around the 17th century has a strong influence on the lifestyle of people in urban Java. In the Weltevreden area, the people's lifestyle influenced by Indis culture is visible in the way they dress, speak, enjoy music and entertainment carried out by European and the native people. Apart from Europe, the lifestyle of the people in the Weltevreden area also experiences mixing and adaptation because there are other groups such as the natives, Chinese and Arabs who live in the area. The lifestyles between these groups were different based on the cultural background of each group.